El pasajero aéreo desprotegido: obstáculos a la tutela judicial en litigios transfronterizos por incumplimientos de las compañías aéreas (A propósito de la STJUE de 9 julio 2009, Rehder, As. C-204/08) - Maestre Casas, Pilar (CUADERNOS DE DERECHO TRANSNACIONAL, 2011)
In order to fix jurisdiction in suits against airlines for compensation in case of cancellation of flights, the Court of Justice of the European Union resolved the problem of determining the place where the service was rendered in the case of contractual obligations deriving from an international air transport contract. The solution given [‘in the case of air transport of passengers from one Member State to another Member State, carried out on the basis of a contract with only one airline, which is the operating carrier, the court having jurisdiction to deal with a claim for compensation founded on that transport contract (…) is that, at the applicant’s choice, which has territorial jurisdiction over the place of departure or place of arrival of the aircraft, as those places are agreed in that contract’] may contribute to alleviating the passenger’s lack of protection, as long as the place of departure or the place of arrival coincides with the passenger’s domicile. Otherwise, the passenger still cannot apply to the forum actoris stipulated for consumer contracts despite fulfilling all the circumstances demanded in Article 15 of Regulation 44/2001.